Factor „defences ” in the contemporary architecture of residential housing estate - Kłopotowska, Agnieszka (Budownictwo i Architektura / Civil and Architectural Engineering, 2010)
The defence factor which largely determined the location and shape of historic settlements remains a major determinant of the structure of contemporary global cities. Separated enclaves of guarded housing estates are becoming an extreme sign of their inhabitants’ concern for their own safety. Since they first appeared in Poland, gated communities have enjoyed enormous popularity. The success of this housing model rests above all on the feeling of exclusiveness, achieved through the idea of fencing off. Fear of intruders from the outside appears to be a secondary factor. However, the steadily increasing level of fear effectively fuelled by the sellers of security systems results in more and more sophisticated means of protection of Polish “gated communities”.